On the consequences of Fisk's type magnetic field configuration for galactic cosmic ray modulation - Kobylinski, Z.; Ajabshirizadeh, A.; Wysokinski, A. (Кинематика и физика небесных тел, 2005)
Three-dimensional steady state transport equation of galactic cosmic rays with drift included is solved by means of newly achieved Fortran code in two cases: 1) Fisk’s type of heliospheric magnetic field dominates in the heliosphere; 2) standard Parker field fills the interplanetary space. The spherically symmetric heliosphere bounded at a distance of 100 AU is assumed. In the calculations the parallel and perpendicular diffusion coefficients are proportional to 1/B, anti-symmetric element of the diffusion tensor has the form derived under the assumption of week-scattering. The computed modulated spectra are presented and compared with experimental data (IMP3, IMP8, balloons, and CAPRICE) for the minimum period of solar activity. The best fit is obtained when the index of the power of rigidity in diffusion coefficient formula is less than 0.8.